Características de los donantes, disponibilidad de hemocomponentes y tendencias de marcadores infecciosos en el Banco de Sangre de Loreto, 2018 - 2022 - Paredes Arbildo, Julio (2024)
The evaluation of donors and blood components ensures quality therapy. Objective. To characterize donors, describe the availability of blood components, and analyze trends in transfusion-transmissible infections (TTIs). Methods. A descriptive-retrospective study was conducted using data from the Loreto Regional Blood Donation Center (2018–2022). Applicants aged over 18 years, screened serologically for HIV, hepatitis B, hepatitis C, HTLV, syphilis, and Chagas disease, were included. sociodemographic variables, deferrals, production, disposal of blood components, and TTI prevalence were analyzed through descriptive analysis. Results. In 2022, 72.5% of donors were eligible and 21.9% were deferred (2020), with low hemoglobin as the leading cause (30%). Male participation predominated (74.3%), as did the 25–44 age group (60%). Blood component production increased from 3487 to 7568 units, with red blood cell concentrates being the most prominent (68.7%). Discards totaled 1583 units, primarily due to expiration (68.4%) and TTIs (29.3%). Syphilis was the most common TTI (1.4%), followed by HTLV (0.5%) and Chagas (0.4%). Conclusion. The study evidenced a sustained increase in the production and demand for blood components. The main characteristic of the donors was male predominance and age between 25 and 44 years. The main causes of elimination were expiration and transfusion-transmissible infections (TTIs), with syphilis standing out as the infection with the highest prevalence and the most marked upward trend during the analyzed period.